von Willebrand Factor as a Predictor for Transplant-Associated Thrombotic Microangiopathy - Xu, Zhenzhen (Clin Appl Thromb Hemost, 2020)
Transplant-associated thrombotic microangiopathy (TA-TMA) after hematopoietic stem cell transplantation (HSCT) is a severe complication associated with underlying endothelial damage. Secreted and released von Willebrand factor (vWF) correlates with endothelial cell injury, but its role in predicting prognosis for TA-TMA is unclear. In this prospective study, we evaluated the relationship between vWF and the incidence of TA-TMA after HSCT. A total of 79 consecutive patients undergoing HSCT from August 2016 to June 2018 were enrolled. Twenty-three (29%) patients met the established diagnostic criteria. Patients with TA-TMA had significantly higher nonrelapse mortality compared with those without TA-TMA (78.3% vs 8.9%; P < .001). Multivariable analysis demonstrated that vWF was a predictive biomarker for TA-TMA. The vWF value was higher for the TA-TMA group (mean ± standard deviation, 380.7% ± 78.8% vs 284.9% ± 104.5%; P < .001), and the area under the curve for vWF in the diagnosis of TA-TMA was 0.756. Furthermore, patients with ≥325% vWF had a higher 2-year cumulative hazard of TA-TMA (53.1% ± 8.2% vs 7.5% ± 4.2%; P < .001) and a lower 2-year survival (32.1% ± 9.1% vs 83.7% ± 6.2%; P < .001) compared with those with <325% vWF. CONCLUSION: von Willebrand factor is a useful predictor and prognostic measure for TA-TMA, which may help clinicians identify and manage this life-threatening disease earlier.